Board gender diversity and performance in gazelles: evidence from a sample of Italian private hospitals - Mauro, Marianna; Giancotti, Monica; Ferrari, Elisa Rita; Cattafi, Giulia (Piccola Impresa / Small Business, 2023)
Purpose: This paper examines the influence of board composition in terms of gender diversity on the performance of high-growth firms, offering evidence from the health sector. Methodology: The sample is composed of 27 startups operating in the health sector. Enterprises are born in Italy in 2014 and became gazelles in 2018 or 2019, respectively, in the fourth or fifth year of life. To analyse the effect of board gender diversity, multiple regression models were utilised, using return on assets (ROA) as a measure of financial performance. Findings: Results show that there is a statistically significant and positive relationship between board gender diversity and financial performance. In other words, as the percentage of women on board of directors increases, financial performance grows by approximately 6.41%. Originality of the study: The impact of board gender diversity on firms' performances is widely investigated in the literature. However, this study is original both for the type of firms (gazelles) and for the sector investigated (private hospitals). Practical implications: Managers of high-growth startups may find advantages in including women in executive and board positions. This is particularly relevant for the private healthcare sector, where governance structure plays a key role in achieving performance objectives.